A Different View on the Simple View of Reading. (December 2022) - Apel, Kenn
The simple view of reading (SVR) framework has been used for decades to explain two general component skills considered to contribute to reading comprehension: decoding and linguistic comprehension. In the past, researchers have assessed the linguistic comprehension component using a wide range of language and/or listening comprehension measures that differed from each other. Many of those tasks did not align with the concept of linguistic comprehension originally proposed. Regardless, the studies' outcomes were similar: The SVR model adequately represents the process of reading comprehension. In this article, I propose a common thread that links those diverse measurement tasks: all the tasks measured students' metalinguistic skills. In fact, the findings from these studies mirror those found from investigations directly measuring the influence of language awareness abilities on reading comprehension. I conclude the article with the theoretical and educational implications of taking a different view of the second component of the SVR model.